Sistem Informasi Reservasi Kamar Wisma Atlet Pada DISPORASU Berbasis Android - Rahma Syahri; Triase (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Wisma Athlete is an inn owned by the North Sumatra Provincial Government which is managed by the North Sumatra Youth and Sports Service. Currently, the room reservation process at the athlete's guesthouse is still done manually, guests must come directly to the guesthouse to obtain information and make a reservation. This has problems for the guests and the athletes' guesthouse in terms of time, costs and lack of marketing at the guesthouse. The purpose of this research is to create an Android-based room reservation information system at the Athlete's Guesthouse that can help with this problem. In creating the information system using the Waterfall development method and Unified Modeling Language (UML) tools and in building this information system using the JavaScript programming language, the Veu JS 2.0 framework, and the MySQL database. The result of this research is an Android-based room reservation application. The application that was built can be used as a means so that the general public can find out that at the DISPORASU athlete's guesthouse, not only athletes can make reservations at that place but the general public can also stay at the guesthouse. This application also helps guests to get room information, facilities in the guest house easily, make room reservations online without having to come directly to the guest house and can order food without having to come to the cafeteria in the guest house. This application also helps DISPORASU in managing rooms and helps increase profitability at the guest house